Air‐Stable Lithium Spheres Produced by Electrochemical Plating. (31st August 2018) - Yang, Tingting; Jia, Peng; Liu, Qiunan; Zhang, Liqiang; Du, Congcong; Chen, Jingzhao; Ye, Hongjun; Li, Xiaomei; Li, Yanshuai; Shen, Tongde; Tang, Yongfu; Huang, Jianyu
Abstract: Lithium metal is an ideal anode for next‐generation lithium batteries owing to its very high theoretical specific capacity of 3860 mAh g −1 but very reactive upon exposure to ambient air, rendering it difficult to handle and transport. Air‐stable lithium spheres (ASLSs) were produced by electrochemical plating under CO2 atmosphere inside an advanced aberration‐corrected environmental transmission electron microscope. The ASLSs exhibit a core–shell structure with a Li core and a Li2 CO3 shell. In ambient air, the ASLSs do not react with moisture and maintain their core–shell structures. Furthermore, the ASLSs can be used as anodes in lithium‐ion batteries, and they exhibit similar electrochemical behavior to metallic Li, indicating that the surface Li2 CO3 layer is a good Li + ion conductor. The air stability of the ASLSs is attributed to the surface Li2 CO3 layer, which is barely soluble in water and does not react with oxygen and nitrogen in air at room temperature, thus passivating the Li core.